2021
DOI: 10.1097/rli.0000000000000760
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Imaging Detection of Glucose-Stimulated Zinc Secretion in the Enlarged Dog Prostate as a Potential Method for Differentiating Prostate Cancer From Benign Prostatic Hyperplasia

Abstract: Supplemental digital content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 53 publications
0
10
0
Order By: Relevance
“…The SR-XRF data also showed that glucose promotes the movement of Zn 2+ pools (∼1 mM) from the glandular lumen of the lateral lobe into the stromal/smooth muscle surrounding the glands. More recently, GdL1 was used to detect glucose-stimulated Zn 2+ -secretion in older dogs with clinically diagnosed benign prosthetic hypertrophy (BPH) [86]. This observation is important because in man, differentiation of prostate cancer from BPH tissues on MRI scans can be challenging, so translation of this technology to the clinic could be diagnostically important.…”
Section: Figurementioning
confidence: 99%
“…The SR-XRF data also showed that glucose promotes the movement of Zn 2+ pools (∼1 mM) from the glandular lumen of the lateral lobe into the stromal/smooth muscle surrounding the glands. More recently, GdL1 was used to detect glucose-stimulated Zn 2+ -secretion in older dogs with clinically diagnosed benign prosthetic hypertrophy (BPH) [86]. This observation is important because in man, differentiation of prostate cancer from BPH tissues on MRI scans can be challenging, so translation of this technology to the clinic could be diagnostically important.…”
Section: Figurementioning
confidence: 99%
“…The authors also record a similar association between urinary Zn level and pre-diabetes. It is a possibility that the prostatic Zn gets increasingly secreted out and eventually ends up in urine when levels of blood glucose or dextrose increase [ 188 , 189 ].…”
Section: Resultsmentioning
confidence: 99%
“…Using magnetic resonance imaging with a gadolinium-based Zn-responsive contrast agent and glucose-stimulated Zn secretion has been detected in BPH tissue compared to prostate cancer in a dog model [ 189 ]. If this contrast can be adapted to be used on humans, that will support differentiating BPH from prostate cancer.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Malignant epithelium interacts with other components of the tumor microenvironment and, when corrupted, CAFs induce the Warburg effect, which indirectly or directly results in the production and secretion of important metabolic intermediaries involved in energy production [ 184 ]. Unlike dogs, studies in humans have shown some mechanisms and expression of markers involved in the modulation of PC energy metabolism [ 185 , 186 ]. One of the signaling pathways involved is related to the role of the STAT3 oncogene in the regulation of genes related to cell metabolism [ 187 ].…”
Section: Molecular Biology Of Prostate Cancermentioning
confidence: 99%